O mais além da palavra: quando a imagem cai no abismo e encontra o silêncio - Domingues, Mariana (2014)
This work is part of an investigation into the silence and its repercussions in the image field. Bergman and Tarkovsky were chosen to situate a particular type of film, it appears that in close dialogue with psychoanalysis and the subject's relation to the image